Guillermo Castro Talavera: capstone - Talavera, Guillermo Castro, artist (Colorado State University. Libraries, 2026)
The artist's statement: In art, the two most important concepts are concept and form. Without a concept, a piece of art has no purpose nor a soul to be interpreted. Without a form, a piece of art has no way of existing outside the mind of the artist; in which case, it is not an artwork at all, it is just an idea. There always needs to be a coexistence of the two; how that balanced coexistence appears in art is up to the sensibilities of the artist. Personally, my sensibilities favor the form over the concept. I believe that in an impactful artwork, what impacts the viewer is how the artwork exists more than why it exists. In my work, I like using pen and ink to draw expressive figures. If what is to be expressed are human ideas, the human body is the best vehicle to convey them. I use pen and ink because the formal challenge of making a drawing with a wide range of values while only being able to make a mark with my darkest value is attractive to me.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: drawing